(untitled) (Bangladesh Pharmaceutical Journal, 2012)
Many developmentally important Receptor Like Kinases (RLKs), also known as receptor kinases have been shown to play independent roles in plant defence. In order to investigate the role of Arabidopsis CRINKLY4 (ACR4) in plant defence mechanism, pathogen challenge experiments were carried out. It was found that ACR4 knockout leaves show reduced susceptibility to the necrotrophic pathogen, Botrytis cinerea. It is therefore possible that the ACR4 receptor might interact with other proteins that regulate specific defence responses. Reduced susceptibility of ACR4 mutant to B. cinerea could also be due to the possible epidermal defect of acr4 leaves. A detailed study of the cuticular lipid composition of acr4 leaves may help ascertain whether epidermal defects in acr4 leaves are responsible for resistance against B. cinerea. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12576 Bangladesh Pharmaceutical Journal 15(2): 127-130, 2012